From substrate limitation to competition control: straw input regulates sulfate-mediated suppression of methanogenesis in paddy soils - Tianzhuo Cheng; Wankun Pan; Wolfgang Wanek; Che Tan; Roland Bol; Yongchao Liang; Qingxu Ma (Soil Biology and Biochemistry, 2026)

A multisource weakly supervised high-resolution crop mapping framework based on low-resolution noise labels - Hongyan Che; Jun Ma; Yaozhong Pan; Xiufang Zhu; Xingsheng Xia; Yinda Wang; Lingang Wang; Yongsheng Huang (Computers and Electronics in Agriculture, 2026)

Marine polysaccharide-based multifunctional composite sponge for rapid hemostasis and enhanced infected wound healing - Yinuo Fan; Kaihua Liu; Chunxiao Wang; Xinyu Zhang; Ning Wang; Shuying Liu; Xianjiao Shao; Yuju Che; Panpan Pan; Lin Xia; Jingdi Chen (Marine Life Science & Technology, 2026)

Thermal dynamics of an intermittent subtropical stream controlled by surface water-groundwater interactions: evidence from distributed temperature sensing and heat-budget modeling - Yen-Wei Pan; Yu-Cheng Chen; Tsung-Yu Lee; Yung-Chia Chiu; Shao-Yu Hsu; Che-Ming Chen (Environmental Monitoring and Assessment, 2026)

Corrigendum to “A multisource weakly supervised high-resolution crop mapping framework based on low-resolution noise labels” [Comput. Electron. Agric. 251 (2026) 112003] - Hongyan Che; Jun Ma; Yaozhong Pan; Xiufang Zhu; Xingsheng Xia; Yinda Wang; Lingang Wang; Yongsheng Huang (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Pristine and iron-engineered animal- and plant-derived biochars enhanced bacterial abundance and immobilized arsenic and lead in a contaminated soil” [Sci. Total Environ. (763) 2021, 144218] - He Pan; Xing Yang; Hanbo Chen; Binoy Sarkar; Nanthi Bolan; Sabry M. Shaheen; Fengchang Wu; Lei Che; Yibing Ma; Jörg Rinklebe; Hailong Wang (Science of The Total Environment, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Scale effect research on cavity evolution and impact load characteristics during high-speed water entry - Yao Shi; Peiqi Che; Qiaogao Huang; Guang Pan (Ocean Engineering, 2026)

Fe-doped BiOBr nanosheets vertically grown on TiO2 nanotube arrays for photoelectrocatalytic treatment of reclaimed water - Gui Yang; Yu Yan; Xing Wan; Huan He; Jingxian Mei; Meina Zhu; Huachao Che; Junhui Zhang; Juhong Zhan; Xiaoyong Wu; Bin Huang; Xuejun Pan (Journal of Environmental Sciences, 2026)

Repurposing tumor-derived extracellular vesicles with an adhesive carboxymethyl chitosan-based hydrogel for spinal cord injury repair - Kuan-Lin Wang; Yu-Che Hsiao; Wen-Yu Pan; Chun-Jung Lin; Chieh-Cheng Huang; Yu-Jung Lin (Carbohydrate Polymers, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Tetrabromobisphenol A and Cadmium Chloride Induced Hepatic Oxidative Stress and Autophagy Inhibition in Rats - Rongjing Sun; Jing Tian; Li Che; Tianyang Liu; Huibin Jin; Haonan Zhao; Jin Chen; Nianping Zhang; Xi Kang; Luqing Pan; Piaoye Wu; Bei Liu; et al. (Biological Trace Element Research, 2026)

Synergistic LiNO3/FEC modification to nonflammable LiOTf-TMP electrolyte for durable lithium metal batteries - Chun-Jern Pan; Chia-Ho Liu; Shih-Che Lin; Chun-I Lee; Chia-Hsin Wang; Bing-Joe Hwang (Chemical Engineering Journal, 2026)

Reconciling the reactivity-biocompatibility trade-off in nanoscale zero-valent iron with an amorphous core and pseudocapacitive biointerface for enhanced anaerobic methanogenesis - Linxuan Che; Ziruo Wang; Hui Xu; Lu Lv; Weiming Zhang; Bingcai Pan; Qingran Zhang; Ming Hua (Water Research, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Engineering active oxygen vacancy sites in WO3@COF for efficient photocatalytic hydrogen peroxide production - Yuheng Zhang; Qixin Pan; Chaojie Xing; Jiali Lu; Yunkai Sun; Xiaoqiang Xue; Wei Wang; Che Zhao; Rui Wang (Chemical Engineering Journal, 2026)

A novel spectral and phenological composite index for the early automatic mapping of potatoes from Sentinel-2 multi-temporal images - Lingang Wang; Yuan Gao; Yaozhong Pan; Wenjie Feng; Xingsheng Xia; Chuanwu Zhao; Xuechang Zheng; Hongyan Che; Yongsheng Huang; Xuehui Hou (Computers and Electronics in Agriculture, 2026)

Oxygen vacancy enriched alumina supported Ni nanocatalysts for highly selective acetylene hydrogenation - Hedan Yao; Yuanjun Che; Dong Huang; Yi Qin; Yuchen Niu; Wenhong Li; Liuyi Pan; Dong Li (Chemical Engineering Journal, 2026)

Simultaneous enhancement of anaerobic decontamination and energy recovery in azo dye wastewater by sulfur-modified nanoscale zero-valent iron: Insights from continuous-flow operation and microbial ecology - Ziruo Wang; Linxuan Che; Weiming Zhang; Lu Lv; Bingcai Pan; Ming Hua (Journal of Environmental Chemical Engineering, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Long-term effects and mechanisms of sulfur-modified nanoscale zero-valent iron in enhancing anaerobic treatment of highly toxic wastewater containing 2,4-dichlorophenol - Linxuan Che; Yuxin Xiao; Ziruo Wang; Weiming Zhang; Bingcai Pan; Ming Hua (Bioresource Technology, 2025)

Study on Frost Deformation Characteristics of Transversely Isotropic Rocks Under Unidirectional Freeze–Thaw Cycles - Hanqing Lu; Weixing Bao; Yan Yin; Bowen Che; Zhenhua Pan (Rock Mechanics and Rock Engineering, 2025)

Climate teleconnections among the Earth’s three poles - Anmin Duan; Xin Li; Wenting Hu; Tao Che; Jun Hu; Yuzhuo Peng; Chao Zhang; Die Hu; Yuheng Tang; Zhulei Pan; Qilu Wang; Guoxiong Wu (Science Bulletin, 2025)

Sulfur-modified nanoscale zero-valent iron promotes efficient start-up of anaerobic treatment for azo dye wastewater: Synergistic bioaugmentation and extracellular electron transfer enhancement - Ziruo Wang; Linxuan Che; Yongyan Zhou; Weiming Zhang; Lu Lv; Bingcai Pan; Ming Hua (Journal of Water Process Engineering, 2025)

Bioinspired multifunctional conductive hydrogel based on hydroxypropyl methyl cellulose for flexible sensors - Hongtian Yan; Haonan Gu; Shizhou Lu; Fanjun Meng; Qinglin Ma; Xiang Xing; Shihui Pan; Yuju Che (Carbohydrate Polymers, 2025)

Synergistic role of potassium ferrate and calcium peroxide for significantly enhancing the anaerobic digestion of waste activated sludge: Promoting mechanisms on organic biodegradability and methane production - Linxuan Che; Ziruo Wang; Weiming Zhang; Bingcai Pan; Ming Hua (Chemical Engineering Journal, 2025)

Assessment of Egg Yolk IgY Antibodies Against Live or Inactivated Aeromonas hydrophila for Polyvalent Passive Immunization in Goldfish (Carassius auratus) - Pan Cui; Jing Chen; Huihui Xiao; Xixian Che; Shujun Sun; Zijian Ma; Juan Lu; Gaoxiao Xu; Xiang Liu (Fishes, 2025)
Egg yolk IgY antibody has significant application potential in aquaculture as a form of passive immunotherapy against various bacterial infections owing to its capacity for large-scale and cost-effective production. In this research, laying hens were immunized with live or inactivated Aeromonas hydrophila to produce IgY antibodies. Following this, experiments were carried out to assess the passive immune protection rates of the two types of IgY antibodies when used to immunize goldfish (Carassius auratus), which were then infected with A. hydrophila or Aeromonas veronii. ELISA experiments were conducted to demonstrate the interaction between the IgY antibodies and the bacteria. The kidneys of C. auratus were coated on a Luria–Bertani (LB) medium to evaluate bacterial content. The leukocyte phagocytosis was detected by a cell phagocytosis assay. The serum of C. auratus was used to assess the expression of antioxidant factors, and a qRT-PCR was conducted to evaluate the mRNA expression of inflammatory factors in visceral tissue. Furthermore, histopathology and immunofluorescence analysis were performed to evaluate the structural integrity, apoptosis, and DNA damage of visceral tissues. The results indicated that the live or inactivated A. hydrophila IgY antibodies exhibited passive immune protection rates against A. hydrophila and A. veronii and could recognize these two bacteria in vitro. Additionally, these two IgY improved the phagocytic ability of leukocytes, diminished renal bacterial concentration, and decreased the levels of antioxidant factors and mRNA expression of inflammatory factors. Meanwhile, the two IgY antibodies did not cause any pathology of the kidney, spleen, and intestine, and decreased the levels of DNA damage factor (γH2A.X) and cell apoptosis factor (p53) in renal tissue. Therefore, live and inactivated A. hydrophila IgY antibodies can resist bacterial infections, with live bacteria IgY providing greater protection than inactivated bacteria IgY. Further, A. hydrophila is an aquatic pathogen that causes minimal damage to laying hens, and the immunity of live A. hydrophila conforms to animal welfare. Altogether, live A. hydrophila IgY antibody can serve as a polyvalent passive immune vaccine candidate in aquaculture.

Estimating the Permeability–Depth Relation of Slate Formation for Geothermal Project - Xuan-Xinh Nguyen; Che-Wei Yeh; Tan-Minh Le; Jia-Jyun Dong; Chih-Hsi Liu; Chi-Ping Pan (Rock Mechanics and Rock Engineering, 2025)

Polyvalent immunoprotection of protein, DNA and IgY antibody vaccines of Vibrio fluvialis outer membrane protein VF08100 in fish - Huihui Xiao; Saixing Duan; Pan Cui; Jing Chen; Xixian Che; Juan Lu; Juan Wang; Guoping Zhu; Yong Liu; Xiang Liu (Fish & Shellfish Immunology, 2025)

MIL-100(Fe)-derived Mg/Fe layered double hydroxides composite millimeter-scale aerogel beads for phosphate adsorption from real domestic wastewater - Yubo Pan; Ruijie Che; Keren Lu; Linrui Li; Mingxing Shi; Mingzhu Xia; Fenghe Wang; Fengyun Wang (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

The promoted Fenton degradation of norfloxacin by a S-ZnO modified MnFe2O4 with micro-acidic environment - Ting Pan; Danni Wang; Yanyu Song; Yongdi Liu; Long D. Nghiem; Jun Duan; Chengdan Che; Xianbo Sun; Zhengqing Cai (Chemical Engineering Journal, 2025)

Corrigendum to “Pristine and iron-engineered animal- and plant-derived biochars enhanced bacterial abundance and immobilized arsenic and lead in a contaminated soil” [Sci. Total Environ. 763 (2021) 144218] - He Pan; Xing Yang; Hanbo Chen; Binoy Sarkar; Nanthi Bolan; Sabry M. Shaheen; Fengchang Wu; Lei Che; Yibing Ma; Jörg Rinklebe; Hailong Wang (Science of The Total Environment, 2024)

MiR-497-5p ameliorates the oxyhemoglobin-induced subarachnoid hemorrhage injury in vitro by targeting orthodenticle homeobox protein 1 (Otx1) to activate the Nrf2/HO-1 pathway - Jun Zhu; Enyu Pan; Lujun Pang; Xiwei Zhou; Yanjun Che; Zhao Liu (Molecular Genetics and Genomics, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

Allergenicity risk in animal-based food proteins: Source, dietary factors effect, allergen detection and processing modification methods - Yanxiang Bi; Changqi Liu; Fei Pan; Wenjun Peng; Xiaoming Fang; Huilian Che; Wenli Tian (Trends in Food Science & Technology, 2024)

Tunicate cellulose nanocrystals strengthened injectable stretchable hydrogel as multi-responsive enhanced antibacterial wound dressing for promoting diabetic wound healing - Shengming Hua; Yujie Zhang; Yifei Zhu; Xin Fu; Lingtao Meng; Lihua Zhao; Lingming Kong; Shihui Pan; Yuju Che (Carbohydrate Polymers, 2024)

Enhanced sensitivity of spectral CT imaging in vivo by using Ytterbium chelate - Chunmei Yang; Didi Gu; Xin Zhu; Pan Han; Liping Pan; Xiaoling Che; Xinyao Chen; Qiuyu Meng; Guidong Dai; Lu Yang (Chemical Engineering Journal, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Construction of chiral magnetic structure with enhancement in magnetic coupling for efficient Low-Frequency microwave absorption - Hao Zhang; Yongpeng Zhao; Mingyue Yuan; Chen Sun; Hui Huang; Yuchen Jiang; Zeng Fan; Renchao Che; Lujun Pan (Chemical Engineering Journal, 2024)

Study on the cavity evolution and load characteristics of large projectile during high-speed water entry - Peiqi Che; Yao Shi; Hairui Zhao; Yilan Yu; Guang Pan (Ocean Engineering, 2024)

New insight into the effects of p-benzoquinone on photocatalytic reduction of Cr(VI) over Fe-doped g-C3N4 - Shi-Wen Lv; Jialu Pan; Xiaoran Wang; Yifan Shao; Yanqing Cong; Lin Che (Environmental Research, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

Effects of occupational exposure to metal fume PM2.5 on lung function and biomarkers among shipyard workers: a 3-year prospective cohort study - Huan Minh Tran; Ching-Huang Lai; Wei-Liang Chen; Chung Ching Wang; Che-Wei Liang; Chi-Yu Chien; Chih-Hong Pan; Kai-Jen Chuang; Hsiao-Chi Chuang (International Archives of Occupational and Environmental Health, 2024)
Objective This study investigates the associations of α1-antitrypsin, inter-α-trypsin inhibitor heavy chain (ITIH4), and 8-isoprostane with lung function in shipyard workers exposed to occupational metal fume fine particulate matter (PM 2.5 ), which is known to be associated with adverse respiratory outcomes. Methods A 3-year follow-up study was conducted on 180 shipyard workers with 262 measurements. Personal exposure to welding fume PM 2.5 was collected for an 8-h working day. Pre-exposure, post-exposure, and delta (∆) levels of α1-antitrypsin, ITIH4, and 8-isoprostane were determined in urine using enzyme-linked immunosorbent assays. Post-exposure urinary metals were sampled at the beginning of the next working day and analyzed by inductively coupled plasma-mass spectrometry. Lung function measurements were also conducted the next working day for post-exposure. Results An IQR increase in PM 2.5 was associated with decreases of 2.157% in FEV 1 , 2.806% in PEF, 4.328% in FEF 25% , 5.047% in FEF 50% , and 7.205% in FEF 75% . An IQR increase in PM 2.5 led to increases of 42.155 µg/g in ∆α1-antitrypsin and 16.273 µg/g in ∆ITIH4. Notably, IQR increases in various urinary metals were associated with increases in specific biomarkers, such as post-urinary α1-antitrypsin and ITIH4. Moreover, increases in ∆ α1-antitrypsin and ∆ITIH4 were associated with decreases in FEV 1 /FVC by 0.008% and 0.020%, respectively, and an increase in ∆8-isoprostane resulted in a 1.538% decline in FVC. Conclusion Our study suggests that urinary α1-antitrypsin and ITIH4 could indicate early lung function decline in shipyard workers exposed to metal fume PM 2.5 , underscoring the need for better safety and health monitoring to reduce respiratory risks. Graphical abstract

Trajectory Planning for Cooperative Double Unmanned Surface Vehicles Connected with a Floating Rope for Floating Garbage Cleaning - Mengdi Zhang; Xiang Zheng; Jianhua Wang; Zijun Pan; Wenbo Che; Haozhu Wang (Journal of Marine Science and Engineering, 2024)
Double unmanned surface vehicles (DUSVs) towing a floating rope are more effective at removing large floating garbage on the water’s surface than a single USV. This paper proposes a comprehensive trajectory planner for DUSVs connected with a floating rope for cooperative water-surface garbage collection with dynamic collision avoidance, which takes into account the kinematic constraints and dynamic cooperation constraints of the DUSVs, which reflects the current collection capacity of DUSVs. The optimal travel sequence is determined by solving the TSP problem with an ant colony algorithm. The DUSVs approach the garbage targets based on the guidance of target key points selected by taking into account the dynamic cooperation constraints. An artificial potential field (APF) combined with a leader–follower strategy is adopted so that the each USV passes from different sides of the garbage to ensure garbage capturing. For dynamic obstacle avoidance, an improved APF (IAPF) combined with a leader–follower strategy is proposed, for which a velocity repulsion field is introduced to reduce travel distance. A fuzzy logic algorithm is adopted for adaptive adjustment of the desired velocities of the DUSVs to achieve better cooperation between the DUSVs. The simulation results verify the effectiveness of the algorithm of the proposed planner in that the generated trajectories for the DUSVs successfully realize cooperative garbage collection and dynamic obstacle avoidance while complying with the kinematic constraints and dynamic cooperation constraints of the DUSVs.

Portable and reversible smart labels for non-destructive detection of seafood freshness via amine-response fluorescent ionic liquids - Siying Che; Shujia Pan; Xinxiang Shao; Wei He; Qijia Shou; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Experimental study on multi-scale damage and deterioration mechanism of carbonaceous slate under freeze-thaw cycles - Hanqing Lu; Weixing Bao; Yan Yin; Xun Sun; Huizhou Li; Zhenhua Pan; Bowen Che (Bulletin of Engineering Geology and the Environment, 2023)

Petrology and mineralogy of the martian olivine gabbroic shergottite Northwest Africa 13581: Insights into the enriched martian mantle source - Yunhua Wu; Weibiao Hsu; Shiyong Liao; Zhiyong Xiao; Xiaochao Che; Lili Pan; Ye Li; Shaolin Li (Geochimica et Cosmochimica Acta, 2023)

The effect of maternal consumption of high-fat diet on ovarian development in offspring - Wenyan Wei; Feng Qin; Junjie Gao; Junlei Chang; Xujing Pan; Xuemei Jiang; Lianqiang Che; Yong Zhuo; De Wu; Shengyu Xu (Animal Reproduction Science, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

Enhancing viability of dried lactic acid bacteria prepared by freeze drying and spray drying via heat preadaptation - Huan Yang; Pan Huang; Liying Hao; Yulan Che; Shirong Dong; Zihao Wang; Chongde Wu (Food Microbiology, 2023)

Exploring Chromium Ore Consumption: New Perspectives from Hybrid CEEMDAN–S-Curve Modeling - Zhaoshuai Pan; Zhaozhi Zhang; Dong Che (Natural Resources Research, 2023)

Effect of dense phase carbon dioxide treatment on the flavor, texture, and quality changes in new-paocai - Yage Xing; Rumeng Yi; Tianyi Yue; Xiufang Bi; Lin Wu; Hongjie Pan; Xiaocui Liu; Zhenming Che (Food Research International, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)

Thermal performance of a window shutter with a phase change material as a passive system for buildings in warm and cold climates of México - M. Che-Pan; E. Simá; A. Ávila-Hernández; J. Uriarte-Flores; R. Vargas-López (Energy and Buildings, 2023)

Enhanced desalination and water transport performance of polyelectrolyte-modified ‘holey’ graphene oxide film - Feng Liu; Qingwen Long; Guiquan Che; Zhihao Zhang; Mick Cooper; Jing Zhang; Gang Pan; Wentao Jiao (Journal of Cleaner Production, 2023)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

UBE2R2-AS1 Inhibits Xenograft Growth in Nude Mice and Correlates with a Positive Prognosis in Glioma - Wu Xu; Dan-dan Che; Liang Chen; Sheng-qing Lv; Jun Su; Jun Tan; Qing Liu; Ya-wen Pan (Journal of Molecular Neuroscience, 2021)

An approach for improving the NRLMSISE-00 model using a radiosonde at Golmud of the Tibetan Plateau - Yaru Dai; Weilin Pan; Xiong Hu; Zhixuan Bai; Chao Ban; Hengheng Zhang; Yunfei Che (Meteorology and Atmospheric Physics, 2020)

Large paleo-rockslide induced by buckling failure at Jiasian in Southern Taiwan - Che-Ming Yang; Keng-Hao Kang; Shun-Hsing Yang; Kuo-Wei Li; Hui-Jung Wang; Yin-Tsan Lee; Kuei-Kun Lin; Yii-Wen Pan; Jyh-Jong Liao (Landslides, 2020)

Heterologous expression and purification of BtCspB, a novel cold-shock protein-like bacteriocin from Bacillus thuringiensis BRC-ZYR2 - Xin Jin; Junmin Yao; Haili Fan; Yucheng Che; Jieru Pan; Lingling Zhang; Xiaohong Pan; Ivan Gelbič; Tianpei Huang; Xiong Guan (World Journal of Microbiology and Biotechnology, 2019)

Hunting for cultivable Micromonospora strains in soils of the Atacama Desert - Lorena Carro; Valeria Razmilic; Imen Nouioui; Lee Richardson; Che Pan; Patrycja Golinska; Juan A. Asenjo; Alan T. Bull; Hans-Peter Klenk; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

In situ determination of hydraulic conductivity in Yangtze Delta deposits using a modified piezocone model - Mingfei Zhang; Liyuan Tong; Yijun Yang; Hongbo Che; Huangsong Pan (Bulletin of Engineering Geology and the Environment, 2018)

Determining an Optimal Action Portfolio for Water Resource Management by Using Stochastic Programming - Chih-Chao Ho; Chen-Che Pan; Liang-Cheng Chang (Water Resources Management, 2017)

The K+–Cl− Cotransporter KCC2 and Chloride Homeostasis: Potential Therapeutic Target in Acute Central Nervous System Injury - Haijian Wu; Xiaoru Che; Junjia Tang; Feiqiang Ma; Kun Pan; Mingfei Zhao; Anwen Shao; Qun Wu; Jianmin Zhang; Yuan Hong (Molecular Neurobiology, 2016)

Investigating the Effects of Seepage-Pores and Fractures on Coal Permeability by Fractal Analysis - Yidong Cai; Dameng Liu; Zhejun Pan; Yao Che; Zhihua Liu (Transport in Porous Media, 2016)

Stability and cytotoxicity of angiotensin-I-converting enzyme inhibitory peptides derived from bovine casein - Wei Wu; Pan-pan Yu; Feng-yang Zhang; Hong-xia Che; Zhan-mei Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Development of monoclonal antibody-based galactomannoprotein antigen-capture ELISAs to detect Aspergillus fumigatus infection in the invasive aspergillosis rabbit models - Z.-Y. Wang; J.-P. Cai; L.-W. Qiu; W. Hao; Y.-X. Pan; E. T. K. Tung; C. C. Y. Lau; P. C. Y. Woo; S. K. P. Lau; K.-Y. Yuen; X.-Y. Che (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Denbinobin induces apoptosis by apoptosis-inducing factor releasing and DNA damage in human colorectal cancer HCT-116 cells - Tzu-Hsuan Chen; Shiow-Lin Pan; Jih-Hwa Guh; Chien-Chih Chen; Yao-Ting Huang; Hui-Chen Pai; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)